Viktor Oleksiyovich Presnov and his main contribution to the physics of semiconductors and electronic techniques. To the 100th anniversary of his birthday - Ptashchenko, O.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
The name of Viktor Oleksiyovich Presnov is tightly bound with investigations of properties inherent to glass and electrovacuum ceramics, especially with his studies aimed at the nature of mechanically hard and vacuum-tight coupling of glass and ceramics with metal.